2018
DOI: 10.1007/s00520-018-4355-2
|View full text |Cite
|
Sign up to set email alerts
|

The experiences of older caregivers of cancer patients following hospital discharge

Abstract: These findings highlight psychosocial changes that caregivers experience over the 2-week time period following hospital discharge. Implications include the need to identify interventions to better prepare caregivers for the post-discharge period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding the year of publication, 36 out of 62 articles were published in 2017 and 28 in 2018. Countries where the respective studies were conducted were the USA/Canada ( n = 23) [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31], Scandinavia ( n = 7) [32,33,34,35,36,37,38], UK ( n = 4) [39,40,41,42], Germany ( n = 4) [43,44,45,46], Southern Europe (Italy, Portugal, Spain; n = 8) [47,48,49,50,51,52,53,54], East Asia (Japan, China, Korea, Taiwan; n = 4) [55,56,57,58,59,60], Australia/New Zealand ( n = 4) [61,62,63,64], other ( n = 4) [65,66,67,68], and multinational ( n = 2) [69,70].…”
Section: Resultsmentioning
confidence: 99%
“…Forty-seven studies reported on relatives of advanced cancer patient’s [9,10,11,13,15,16,17,18,19,20,21,22,23,24,26,27,28,29,30,31,32,34,36,37,38,39,42,43,44,46,47,48,49,50,51,52,53,55,56,57,58,59,60,61,65,66,67] and 15 studies included relatives of mixed patient samples [12,14,25,33,35,40,41,45,54,62,63,64,68,69,70]. The environment in which the patient received palliative or hospice care were home care in 18 studies [10,14,25,26,27,30,3...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Five studies were conducted in the USA [ 24 26 , 28 , 29 ], two in Israel [ 30 , 31 ], two in Australia [ 32 , 33 ], two in China [ 34 , 35 ], and the rest in various individual countries. Nine studies were qualitative [ 23 25 , 29 , 32 , 34 , 36 38 ], five studies were cross-sectional [ 26 , 31 , 33 , 35 , 39 ], and three were mixed-methods [ 28 , 30 , 40 ]. All included studies were published between 1994 [ 30 ] and 2021 [ 24 , 40 ].…”
Section: Resultsmentioning
confidence: 99%